Immunomodulatory and Growth Promoting Effect of Dietary Fenugreek Seeds in Fingerlings of Common Carp (Cyprinus carpio Lin.) - Kumar, Amresh; Vasmatkar, Pashupat; Baral, Pratibha; Agarawal, Sanjeev; Mishra, Ashutosh (Fishery Technology, 2017)
The aim of the study was to determine theimmunomodulatory effect of dietary intake offenugreek (Trigonella foenumgraecum L.), seed powderon common carp (Cyprinus carpio Lin.). The dietscontaining 5, 10 and 20 g fenugreek kg-1 of dry feedat the rate of 5% of total body weight was fed tofish for 90 days. Experimental fish stock waschallenged intra-peritoneally with Aeromonashydrophila. Total erythrocyte count, haemoglobincount, total serum protein, albumin and globulincontent were determined. Results indicate that thevalues of these parameters were significantly enhancedin fenugreek supplemented groups particularlyin 20 mg kg-1of body weight. Highest lysozymeand nitrobluetetrazolium activity were 65.16 Â± 0.585and 0.989 Â± 0.004 respectively in 10 g kg-1 postchallenge group. The survival percentage andspecific growth rate was higher (98.34%) in 20 mgkg-1 group with respect to control. Furthermore, theantibacterial activity of fenugreek methanolic extractwas also observed against two fish pathogens;Aeromonas hydrophila and Pseudomonas liquefaciens.The findings clearly indicate that the incorporationof fenugreek in diet of common carp fingerlingsenhances the non-specific immunity which increasestheir resistance against infection in fish, suggestingits use in fish diet as a health supplement.